2020
DOI: 10.1002/jsfa.10521
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt‐60 and electron beam irradiation‐induced lipid oxidation in largemouth bass (Micropterus salmoides)

Abstract: BACKGROUNDIrradiation can cause lipid oxidation of fish. This study aimed to examine the effect of radiation (method, dose and dose rate) on the acid value (AV), peroxide value (PV), thiobarbituric acid reactive substances (TBARS) content and fatty acid profile of fresh and freeze‐dried largemouth bass flesh.RESULTSAV, PV and TBARS presented a dose‐dependent increase in fish meat for both cobalt‐60 (60Co) and electron beam (EB) irradiation. With a 6 kGy dose of radiation, all measured indices in the 60Co group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Li et al. (2020) utilized 27Co60 (0, 3, and 6 kGy) and EB (0, 3, and 6 kGy) on largemouth bass ( Micropterus salmoides ) and observed that lipid oxidation increased with higher radiation doses, especially with 60 Co radiation, which had a more pronounced effect on lipid oxidation than EB radiation. Irradiation at 6 kGy resulted in an increase in free fatty acids and primary and secondary lipid oxidation products in largemouth bass.…”
Section: Characteristics Bacteriostatic Mechanism and Applications Of...mentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al. (2020) utilized 27Co60 (0, 3, and 6 kGy) and EB (0, 3, and 6 kGy) on largemouth bass ( Micropterus salmoides ) and observed that lipid oxidation increased with higher radiation doses, especially with 60 Co radiation, which had a more pronounced effect on lipid oxidation than EB radiation. Irradiation at 6 kGy resulted in an increase in free fatty acids and primary and secondary lipid oxidation products in largemouth bass.…”
Section: Characteristics Bacteriostatic Mechanism and Applications Of...mentioning
confidence: 99%
“…As storage time increases, only a few bacterial species (e.g., Shewanella spp., Pseudomonas spp., Photobacterium spp., and Brochotrix spp.) become dominant (Huina et al., 2022; Li et al., 2020; Lou et al., 2021; Parlapani et al., 2023; Zhuang et al., 2022), ultimately leading to spoilage. These bacteria are known as specific spoilage organisms (SSOs) and are involved in degrading muscle and connective tissue proteins into amino acids and peptides, as well as catabolizing nucleotides, carbohydrates, and nitrogen compounds.…”
Section: Introductionmentioning
confidence: 99%
“…As vacuum‐packed frozen beef was treated with gamma irradiation, this technology had little effect on the thawing and aging of frozen beef and did not damage its quality (Sales et al ., 2020). High‐dose 60 Co‐γ irradiation reduced the lipid oxidation of Micropterus salmoides and effectively prolong its shelf life (Li et al ., 2020). However, some studies also suggest that irradiation might lead to the oxidation and breakdown of molecules in meat products, such as fatty acids and amino acids, resulting in an unfavourable odour known as an ‘irradiated scent’ and affecting food's overall flavour and scent.…”
Section: Introductionmentioning
confidence: 99%